Prurigo pigmentosa clinically and immunologically mimicking autoimmune bullous disease: A case report - Kita, Kanako; Kurokawa, Ichiro; Hayashi, Daisuke; Hashimoto, Takashi (Frontiers in Medicine, 2022)
A 15-year-old Japanese male noticed brown macules on his back 9 months ago. Initial examination revealed reticulated infiltrative erythema and pigmentation with blisters on the erythema of the back. Histopathology showed blisters with eosinophil infiltration in the epidermis, and direct immunofluorescence showed negative results for immunoglobulin (Ig) G, Ig A, Ig M, and C3 in the epidermal basement membrane zone. Immuno-serological tests revealed the presence of IgG antibodies against BP180, linear IgA disease antigen 1 (LAD-1), and laminin α3. The autoimmune bullous disease was suspected, and prednisolone at a concentration of 20 mg/day (0.3 mg/kg/day) was started. When the prednisolone dose was reduced to 10 mg/day, erythema and blisters recurred. The patient was diagnosed with prurigo pigmentosa based on clinical features and was treated successfully with oral doxycycline hydrochloride hydrate and topical tacrolimus ointment. This is the first case of prurigo pigmentosa with blisters in which autoantibodies to the epidermal basement membrane zone were found, which might be secondary non-pathogenic antibodies.